Transidentität – Entscheidungsfindung und Kontroverse der medizinischen Behandlung im Kindes- und Jugendalter - Döhnert, Mirko (Sprache · Stimme · Gehör, 2025)
Transgender children and adolescents suffer from the phenomenon of a discrepancy between their biological sex and their gender identity. Some of them need support from the medical system. In addition to psychotherapeutic treatment, medical interventions are possible. After a brief introduction to the topic of transgender identity and gender dysphoria, the current state of knowledge concerning medical treatment including the decision-making and the controversy will be presented and discussed. It can be stated, that hormonal treatment should be discussed to alleviate the psychological suffering. All medical interventions must be carefully considered in the context of an informed consent with all parties involved, including the underage children and adolescents. The decision for early hormone treatment for puberty suppression should be made in a multidisciplinary team, after accompanying psychotherapy and if possible in a specialized center. Irreversible medical interventions should be weighed up particularly carefully.
Keywords: Geschlechtsdysphorie; Hormonbehandlung; Pubertätssuppression; Kontroverse